Arctic Geopolitics Revisited. Spatialising Governance in the circumpolar North - Knecht, Sebastian; Keil, Kathrin (The Polar Journal, 2013)
Knecht S, Keil K. Arctic Geopolitics Revisited. Spatialising Governance in the circumpolar North. The Polar Journal . 2013;3(1):178-203. With the Arctic ice barrier melting away due to anthropogenic global warming, Arctic states’ governmental policies will inevitably determine future governance prospects in high northern latitudes. Whether multilateral cooperation will prevail over or at least complement national economic and security ambitions in the vulnerable Arctic ecosystem, is an often spotlighted but principally hypothetical question that lacks empirical depth. To shed light on this issue, we argue that foreign policy strategies on both sides of the Arctic Ocean are underpinned by a distinct “spatial logic” that drives state behaviour in a fuzzy definition of Arctic territory and accounts for recent region-building dynamics. Assessing geopolitical perceptions of the USA, Canada and the Russian Federation unveils the dichotomous nature of Arctic strategies swaying back and forth between “internal” and “common” waters. From this perspective, it is more Canada’s domestically motivated demand for absolute sovereignty that hampers pan-Arctic collaboration rather than Russia’s hegemon-like status as an Arctic actor.